QIRÃ¢â€™AH SIYÃ¢QÃ®YAH NASR HÃ¢MID ABÃ» ZAYD TENTANG HAK-HAK WANITA DALAM AL-QURâ€™AN - Billa, Mutamakkin (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
Starting from the problems that faced by an Egyptian female experts in field of nuclear reactors as well as a lecture at an university who divorced her husband because she refused her husband?s request for pregnancy/childbirth specially the question of divorce judgment ?suddenly? assigned by religious judge based on ?capping? women role only in domestic region of the family or motherhood (al-ummah). Abû Zayd then analyze the concept of women?s right in the Koran including its relationship with the polygamy case. At the end of the discussion paper, the authors citing the opinion of Abû Zayd that regard bad argument of supporting of polygamy parties whe base themselves on interpretations and interpretations of fiqh and argued on the basis of the conditions of contemporary morality. That polygamy is the best way, in the sense of it?s smaller dangers than the adultery especially when it is figured on the social-moral in the west